2016
DOI: 10.18632/oncotarget.9356
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of RANK SNP rs34945627 in breast cancer patients with bone metastases

Abstract: Receptor activator of NF-kB (RANK) pathway regulates bone remodeling and is involved in breast cancer (BC) progression. Genetic polymorphisms affecting RANK-ligand (RANKL) and osteoprotegerin (OPG) have been previously associated with BC risk and bone metastasis (BM)-free survival, respectively. In this study we conducted a retrospective analysis of the association of five missense RANK SNPs with clinical characteristics and outcomes in BC patients with BM. SNP rs34945627 had an allelic frequency of 12.5% in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Possible explanations of the source of increased sRANKL would be from necrotic tissue and resulting proteolysis of transmembrane receptors or upregulation of primary secretion ( Rogers, 2005 ). In this study, we used the sRANKL and OPG as indicators for bone resorption and turnover in line with a previous publication ( Ferreira et al, 2016 ). Further studies are needed to identify the source of sRANKL.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations of the source of increased sRANKL would be from necrotic tissue and resulting proteolysis of transmembrane receptors or upregulation of primary secretion ( Rogers, 2005 ). In this study, we used the sRANKL and OPG as indicators for bone resorption and turnover in line with a previous publication ( Ferreira et al, 2016 ). Further studies are needed to identify the source of sRANKL.…”
Section: Discussionmentioning
confidence: 99%
“…жінок віком від 13 до 90 років. Ураження кісткової системи зустрічається у 13,6 % хворих на цей тип злоякісних новоутворень [1], а солітарне ураження кісткового апарату -у 41 % з них [2].…”
Section: вступunclassified
“…According to the WHO statistics, up to 100 cases of this disease are diagnosed annually per 100 thousand women aged 13 to 90 years. The skeletal system lesions occur in 13.6 % of patients affected by this type of malignancy [1], while solitary lesions of the skeletal system -in 41 % of those ones [2].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Recently, several studies were conducted to study the prognostic factors for BCBM patients. Clinicopathological data, laboratory tests, and genomic data were confirmed as prognostic predictors for BCBM patients, [8][9][10][11][12][13][14][15][16] and several studies aimed to develop prognostic nomograms for BCBM patients. 6,[16][17][18][19] However, elderly BC patients have their own unique characteristics, which suggested that we need to conduct a specific study for this special population.…”
Section: Introductionmentioning
confidence: 99%